HLA-DQA 1 and polymarker locus allele frequencies for Elazig/Turkey - Dulger, HE; Tokdemir, M (Amer Soc Testing Materials, 2000)
[Abstract Not Available]
Keywords: forensic science; DNA typing; population genetics; HLA-DQA1; LDLR; GYPA; HBGG; D7S8; GC; Turkey